What if Firms Could Borrow More? Evidence from a Natural Experiment - James R. Brown; Gustav Martinsson; Christian Thomann (Center for Economic Studies and ifo Institute (CESifo), 2015)
We study the effects of a unique lending program initiated by the Swedish government at the height of the financial crisis that allowed firms to suspend payment of all labor-related taxes and fees. Comprehensive administrative data on all Swedish firms show that firms borrowing from the program have higher rates of debt growth, investment spending, and employment growth compared to otherwise similar firms whose labor taxes were sufficiently low they could not benefit from the program. These results connect the availability of external credit with real activity in entrepreneurial firms in a way that has proved difficult in other settings.
Keywords: G01; G18; G21; G32; L26; O16; 330; credit constraints; financial crisis; debt policy; entrepreneurial finance; employment growth; real activity